Preparation method and application of nitrile rubber belt

By blending butyl rubber with carbon nanotubes and polylactic acid-graphene nanosheet-like ink and building chemical crosslinking and hydrogen bonding structures, the problem of poor performance of traditional nitrile rubber tape in ice-proof, electromagnetic drying resistance and conductivity is solved, and the effect of significantly improving conductivity and electromagnetic shielding effect is achieved.

CN119264495BActive Publication Date: 2025-04-11YANG ZHOU TENGFEI ELECTRIC CABLE & APPLIANCE MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411783276.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-11
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

Traditional nitrile rubber tapes are not ideal for anti-icing, anti-electromagnetic drying and conductive properties.

Method used

The conductivity of the butyl rubber is improved by blending the butyl rubber with carbon nanotubes and polylactic acid-graphene nanosheet-like ink and constructing chemical crosslinking and hydrogen bonding structures.

Benefits of technology

The conductivity and electromagnetic shielding effect of butyl rubber tape are significantly improved, the DC conductivity reaches 7.4×10-3 kW/m2, the electromagnetic interference coefficient reaches 95 dB, and the thermal conductivity is improved to 78.3 Wmk-1, while improving the anti-ice performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264495B_ABST
    Figure CN119264495B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nitrile rubber belts, and specifically discloses a preparation method and application of the nitrile rubber belt, comprising: first adding nano silicon into a mixed solution of ethanol and deionized water, and stirring; adding the nano silicon cleaned in S1 into ethanol, adding gamma-aminopropyltriethoxysilane dropwise, and adding glacial acetic acid to adjust the pH value of the solution to acidity; based on the advantages and characteristics of butyl rubber and carbon nanotubes, the invention blends these components in a system, and constructs chemical crosslinking and hydrogen bond structures to improve the conductivity of the butyl rubber belt; the single-walled carbon nanotubes added to an insulating BR matrix form a conductive network in the polymer, thereby improving the shielding effect of the single-walled carbon nanotubes; after the surface of the conductive butyl rubber belt is dip-coated with a polylactic acid-graphene nano-sheet ink-based coating, the EMI shielding and conductive properties of the composite butyl rubber belt are further enhanced, and the treated butyl rubber belt has a good effect in anti-icing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nitrile rubber belts, and in particular relates to a preparation method and application of a nitrile rubber belt. Background Art

[0002] Conductive elastomeric polymers can be an exciting solution for environmental and EMI, ESD and RF shielding by providing a component that can provide both an environmental seal and an electrical seal. The combination of elastomers with conductive materials creates a multi-material compound that can provide electrical shielding with the superior flexible and stretchable physical properties of elastomers. Stretchability provides an added benefit that they can be used in applications covering curved surfaces, movable parts, and can accommodate circuit boards and other components of various shapes. As a result, elastomers combined with a large number of conductive fillers have been used in the field of flexible electronics as well as shielding applications in the aerospace, semiconductor and medical industries. The correct selection of conductive fillers is essential to obtain the desired electrical and physical properties. Among elastomers, butyl rubber (BR) is selected as the matrix due to its good oxidation, ozone and chemical resistance, good mechanical flexibility and biocompatibility.

[0003] Carbon nanotubes (CNTs) have received considerable attention as shielding materials due to their unique physical, electrical and chemical properties. Carbon nanotubes are known for their high strength and toughness, good electrical and thermal conductivity, high aspect ratio and low density. Compared with other carbon-based composites, carbon nanotube polymer composites have advantages in ESD applications because of their low filler content, which minimizes the impact on the physical properties of the polymer.

[0004] The design and performance of signal transmission and processing materials for multiple applications such as soft robotics, antennas, printable flexible electronics, wearable electronics, storage devices, tissue engineering, conductive coatings on flexible surfaces, etc. are becoming increasingly attractive. Depending on the application, these coatings can be made into multifunctional coatings so that the surface wettability as well as corrosion resistance, antibacterial properties or de-icing can be customized. Polymer dispersed conductive inks have been widely used in the development of conductive coatings; the anti-icing, anti-electromagnetic drying and conductivity properties of nitrile rubber produced by the traditional preparation process of nitrile rubber tape are not ideal. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a nitrile rubber belt. In view of the advantages of butyl rubber (BR) such as good oxidation resistance, ozone resistance and chemical resistance, good mechanical flexibility, etc., the advantages of carbon nanotube polymer composite materials in ESD (electrostatic discharge) applications, and the characteristics of polylactic acid (PLA)-graphene nanosheet ink-based conductive coatings such as heat conduction and ice elimination, the present invention blends these components in a system and constructs chemical crosslinking and hydrogen bond structures to improve the conductivity of the butyl rubber belt, so as to solve the problems raised in the above-mentioned background technology.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a nitrile rubber belt comprises the following steps:

[0008] S1. First, add nano-silicon to a mixed solution of ethanol and deionized water, stir, separate the nano-silicon using a centrifuge, remove the supernatant, and wash to remove impurities;

[0009] S2, adding the nano-silicon cleaned in the above S1 to ethanol, stirring evenly, adding γ-aminopropyltriethoxysilane (APTES) dropwise under stirring, adding glacial acetic acid to adjust the pH of the solution to acidic, and stirring to obtain an acidic mixture to ensure that γ-aminopropyltriethoxysilane (APTES) and nano-silicon fully react, and then continue to stir the above acidic mixture at room temperature for 12 hours to promote the hydrolysis and polymerization reaction of γ-aminopropyltriethoxysilane (APTES) on the surface of nano-silicon;

[0010] S3, using a centrifuge to separate the nano-silicon modified by the above S2, removing the supernatant, and then washing with ethanol and deionized water for 3 times to remove unreacted γ-aminopropyltriethoxysilane (APTES), and drying the treated nano-silicon in a vacuum oven to remove residual solvent and moisture;

[0011] S4, mixing butyl rubber and maleic anhydride, and reacting them, and then adding nano silicon to the reacted butyl rubber, reacting and stirring;

[0012] S5, dissolving the butyl rubber after the reaction in the above S4 in a toluene solution, adding an activator (zinc oxide and stearic acid), an accelerator (tetramethylthiourea disulfide) and a vulcanizing agent (sulfur), and then performing ultrasonic treatment to obtain a mixture;

[0013] S6, treating the single-walled carbon nanotubes in toluene by ultrasonic treatment, and then adding the resultant to the mixture prepared in S5;

[0014] S7, subjecting the mixture obtained in S6 to ultrasonic treatment again, and drying in a vacuum oven to obtain a dry mixture;

[0015] S8, hot pressing the dry mixture obtained in S7 to make a rectangular sample of nitrile rubber for standby use;

[0016] S9, stirring ethyl acetate and benzyl alcohol at room temperature to obtain a solvent mixture for standby use;

[0017] S10, adding the graphene nanosheets to the solvent mixture of S9, and performing ultrasonic treatment to obtain a mixture for later use;

[0018] S11, adding plasticizer GTA to the mixture obtained in S10, and mechanically stirring the solution until it is completely dissolved;

[0019] S12, adding dimethylsiloxane PDMS and polylactic acid PLA particles to the mixed solution prepared in S11, and magnetically stirring the solution until it is completely dissolved, and finally adding silane coupling agent KH550 and stirring evenly to obtain ink, which is stored for later use;

[0020] S13, wetting the surface of the rectangular sample of nitrile rubber obtained in S8 above with acetic acid solution, and drying it under a fume hood. To avoid shrinkage, the rectangular sample of nitrile rubber is slightly stretched using a strong tape during drying;

[0021] S14, spray the ink prepared in the above S12 on the nitrile rubber substrate processed by the above S13 with a spray gun, apply a layer on the nitrile rubber substrate, and dry it. After the sprayed ink is dried, the composite nitrile rubber after the coating is hot-pressed with a press.

[0022] Preferably, the amount ratio of nano-silicon to ethanol and deionized water in S1 is 1 g:25 mL:25 mL, the stirring time is at least 30 minutes to ensure that the nano-silicon is completely dispersed, and it is washed at least 3 times to remove impurities.

[0023] Preferably, the mass ratio of γ-aminopropyltriethoxysilane (APTES) to nano-silicon in S2 is 1:2, and the pH value of the acidic mixture is 4-5.

[0024] Preferably, the set temperature of the vacuum oven in S3 is 60°C and the drying time is 12 hours.

[0025] Preferably, in S4, the mass ratio of butyl rubber to maleic anhydride is 20:1, the reaction temperature is 90-110°C, the reaction time is at least 60 minutes, the mass ratio of nano-silicon to butyl rubber is 10:1, the reaction temperature is 70-90°C, and the stirring time is at least 30 minutes.

[0026] Preferably, the butyl rubber dissolved in the toluene solution in S5 is 30%wt, the weight ratios of zinc oxide, stearic acid, tetramethylthiourea disulfide, sulfur and butyl rubber are 1:20, 3:100, 1:100 and 1:200 respectively, and the ultrasonic treatment time is at least 30 minutes.

[0027] Preferably, the mass ratio of the single-walled carbon nanotubes to the butyl rubber in S6 is 1-8:100, the ultrasonic treatment time is 30 min, and the speed at which the single-walled carbon nanotubes after ultrasonic treatment are added to the mixture is 1-8 phr.

[0028] Preferably, the ultrasonic treatment time in S7 is at least 60 minutes, the set temperature of the vacuum oven is 60-80° C., and the drying time is at least 12 hours.

[0029] Preferably, in S8, the hot pressing temperature is at least 200° C., the hot pressing pressure is at least 2 MPa, the hot pressing time is 80-100 min, and the thickness of the rectangular nitrile rubber sample is 1 mm.

[0030] Preferably, the mass ratio of ethyl acetate to benzyl alcohol in S9 is 4:1, and the stirring time is at least 2h;

[0031] The graphene nanosheets in S10 are 30%wt and the ultrasonic treatment time is at least 30 minutes;

[0032] In the S11, the plasticizer GTA is 15%wt, the speed of mechanical stirring is ≥550rpm, and the stirring time is at least 5 minutes;

[0033] In the S12, dimethylsiloxane is 20%wt, polylactic acid PLA particles are 35%wt, the speed of magnetic stirring is ≥550rpm, the stirring time is at least 24h, and the silane coupling agent is 5%wt;

[0034] The percentage content of the acetic acid solution in S13 is 100%, and the drying time is at least 15 minutes;

[0035] In the S14, the spraying distance is set to 100 mm, the pressure is 2.0 bar, the coating thickness is 0.150 mm, the drying time is at least 3 hours, the hot pressing temperature is 50-60°C, the hot pressing pressure is at least 2 kPa, and the hot pressing time is at least 2 minutes.

[0036] Preferably, the nitrile rubber tape prepared by the preparation method of the nitrile rubber tape as described above is used in the field of flexible electronics and shielding application materials in the aerospace, semiconductor and medical industries.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] Based on the advantages and characteristics of butyl rubber and carbon nanotubes, the present invention blends these components in a system and constructs chemical crosslinking and hydrogen bond structures to improve the conductivity of the butyl rubber tape; due to the high surface area, aspect ratio, a large number of atoms on the surface and a large number of dangling bonds of the single-walled carbon nanotubes, the single-walled carbon nanotubes added to the insulating butyl rubber BR matrix form a conductive network in the polymer, thereby causing the attenuation of electromagnetic waves, and the free carriers of the single-walled carbon nanotubes increase the dielectric properties and conductivity of the material, thereby improving the shielding effect of the single-walled carbon nanotubes, and the chiral structure of the single-walled carbon nanotubes also enhances the EMI shielding effect, with a DC conductivity of 4.6×10-9 kW / m2, an electromagnetic interference coefficient of 46 dB, a thermal conductivity of 23.1 Wmk-1, a DC conductivity (kW / m2) of 8.6×10-6 kW / m2, and an electromagnetic interference coefficient of 35 dB, and the thermal conductivity is 38.6Wmk-1; after the surface of the conductive butyl rubber belt is dipped in a polylactic acid (PLA)-graphene nanosheet ink-based coating, the EMI shielding and conductive properties of the composite butyl rubber belt are further enhanced, the DC conductivity reaches 7.4×10-3kW / m2, and the electromagnetic interference coefficient reaches 95 dB. At the same time, the thermal conductivity is greatly improved to 78.3 Wmk-1. The treated butyl rubber belt has a good effect in anti-icing. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a physical picture of the uncoated composite butyl rubber prepared in Comparative Example 3 of the present invention;

[0040] Figure 2 This is a SEM microstructure image of the surface of the composite butyl rubber sprayed with a polylactic acid-graphene nanosheet ink-based coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Embodiment 1: A method for preparing a nitrile rubber belt, comprising the following steps:

[0043] S1. Add 2 g of nano-silicon to a mixed solution of 50 ml of ethanol and 50 ml of deionized water, stir for 30 minutes to ensure that the nano-silicon is completely dispersed, separate the nano-silicon using a centrifuge, remove the supernatant, and repeat washing 3 times to remove impurities;

[0044] S2, adding 50 ml of ethanol to the nano-silicon cleaned in the above S1, stirring evenly, adding 1 g of γ-aminopropyltriethoxysilane (APTES) dropwise while stirring to dissolve in 10 ml of ethanol, adding a few drops of glacial acetic acid to adjust the pH of the solution to 4-5, and continuing to stir for 1 hour to ensure that γ-aminopropyltriethoxysilane (APTES) and nano-silicon fully react, and continuing to stir the above mixture at room temperature for 12 hours to promote the hydrolysis and polymerization reaction of γ-aminopropyltriethoxysilane (APTES) on the surface of nano-silicon;

[0045] S3, using a centrifuge to separate the nano-silicon modified by the above S2, removing the supernatant, and then washing with ethanol and deionized water for 3 times to remove unreacted γ-aminopropyltriethoxysilane (APTES), and drying the treated nano-silicon in a vacuum oven at 60° C. for 12 hours to remove residual solvent and moisture;

[0046] S4, 20g of butyl rubber and 1g of maleic anhydride grafted product were mixed, reacted at 100°C for 60 minutes, 2g of nano-silicon was added to the reacted butyl rubber, and stirred at 80°C for 30 minutes;

[0047] S5, dissolving 20 g of the modified BR in S4 in 80 g of toluene solution, then adding 1 g of zinc oxide (activator), 0.6 g of stearic acid (activator), 0.2 g of tetramethylthiourea disulfide (accelerator) and 0.1 g of sulfur (vulcanizing agent), and then ultrasonically treating for 30 min to obtain a mixture;

[0048] S6, 1.2 g of single-walled carbon nanotubes were ultrasonically treated in 20 g of toluene for 30 min, and then added to the rubber matrix at a rate of 6 phr and added to the mixture prepared in S5 above;

[0049] S7, subjecting the mixture obtained in S6 to ultrasonic treatment for 60 minutes, and keeping it dry in a vacuum oven at 60° C. for 12 hours to obtain a dry mixture;

[0050] S8, the dry mixture obtained in above S7 was hot pressed at 200 ℃ under 2MPa pressure for 90min to make a rectangular sample of nitrile rubber with a thickness of 1mm;

[0051] S9, dissolving 80 g of ethyl acetate and 20 g of benzyl alcohol at room temperature for 30 min under stirring with a magnetic stirrer at a speed of 600 rpm to obtain a solvent mixture for standby use;

[0052] S10, adding 3 g of graphene nanosheets to the solvent mixture prepared in S9, and ultrasonically treating the mixture in an ultrasonic bath at 59 kHz for 30 minutes to obtain a mixture for later use;

[0053] S11, adding 1.5 g of plasticizer GTA to the mixture obtained in S10, and mechanically stirring the mixed solution at a speed of 550 rpm for 5 minutes until it is completely dissolved;

[0054] S12, adding 2 g of dimethylsiloxane PDMS and 3.5 g of polylactic acid PLA particles to the mixed solution prepared in S11, and magnetically stirring the solution at 550 rpm for more than 24 hours, and finally adding 0.5 g of silane coupling agent KH550 and stirring evenly to obtain ink, which is stored for later use;

[0055] S13, moistening the surface of the rectangular sample of nitrile rubber prepared in S8 above with 100% acetic acid solution, and drying it under a fume hood for 15 minutes. To avoid shrinkage, use a strong tape to stretch the sample slightly during drying;

[0056] S14. Use a spray gun to spray the ink prepared in the above S12 onto the nitrile rubber substrate treated in step (13). The spraying distance is 100 mm and the pressure is 2.0 bar. A layer is applied on the nitrile rubber with a coating thickness of about 0.150 mm. After spraying the ink and drying for 3 hours, the nitrile rubber is hot-pressed at 55°C using a (Carver) press at 2 kPa and 55°C for 2 minutes and 30 seconds, and molded.

[0057] The SEM microstructure of the surface of the composite butyl rubber sprayed with polylactic acid (PLA)-graphene nanosheet ink-based coating is shown in the attached figure. Figure 2 shown.

[0058] Example 2: The difference between this example and example 1 is that the mass of the single-walled carbon nanotubes in S6 is 0.

[0059] Example 3: The difference between this example and Example 1 is that the mass of the single-walled carbon nanotubes in S6 is 0.4 g.

[0060] Example 4: The difference between this example and Example 1 is that the mass of the single-walled carbon nanotubes in S6 is 0.8 g.

[0061] Example 5: The difference between this example and Example 1 is that the mass of the single-walled carbon nanotubes in S6 is 1.6 g.

[0062] Comparative Example 1: Other conditions were the same as in Example 1, except that step S5 was not performed.

[0063] Comparative Example 2: Other conditions are the same as those in Example 1, except that no graphene nanosheets are added in step S10.

[0064] Comparative Example 3: Other conditions are the same as in Example 1, except that steps S9-S14 are not performed, and the physical picture of the composite butyl rubber without coating is as shown in the attached figure. Figure 1 shown.

[0065] Performance Testing

[0066] The microstructure of the composite nitrile rubber prepared in Example 1 of the present invention is obtained by scanning electron microscopy, and the scanning electron microscope is a S-4800Ⅱ field emission scanning electron microscope FESEM produced in Japan.

[0067] The multifunctional composite nitrile rubber prepared in Examples 1 to 5 and the composite nitrile rubber prepared in Comparative Examples 1 to 3 were tested for anti-electromagnetic interference coefficient performance and electrical conductivity. The specific test results are shown in Table 1:

[0068] Table 1

[0069] sample DC conductivity (kW / m2) Electromagnetic interference coefficient (dB) Thermal conductivity (Wmk-1) Example 1 7.4×10-3 95 78.3 Example 2 8.6×10-6 35 38.6 Example 3 3.5×10-5 48 45.6 Example 4 8.5×10-4 67 52.8 Example 5 9.2×10-3 83 83.1 Comparative Example 1 1.2×10-4 71 67.3 Comparative Example 2 2.5×10-6 58 48.6 Comparative Example 3 4.6×10-9 46 23.1

[0070] It can be seen from the table that the DC conductivity (kW / m2) of the composite nitrile rubber (Example 2) without single-walled carbon nanotubes is 8.6×10-6 kW / m2, the electromagnetic interference coefficient is 35 dB, and the thermal conductivity is 38.6 Wmk-1; while the DC conductivity (kW / m2) of the composite nitrile rubber (Examples 1, 3-5) of single-walled carbon nanotubes is above 3.5×10-5 kW / m2, the electromagnetic interference coefficient is above 48 dB, and the thermal conductivity is above 45.6 Wmk-1. In addition, the butyl rubber is not modified (Comparative Example 1). These properties have decreased, especially the conductive property and electromagnetic shielding property. This is because nanosilicon is a semiconductor material with a certain conductivity. Nanosilicon particles can form a three-dimensional conductive network in butyl rubber, providing a continuous conductive path, thereby significantly improving the conductivity of the composite material. At the same time, the surface of nanosilicon particles has high reflectivity to electromagnetic waves, which can reduce the transmission of electromagnetic waves. At the same time, nano-silicon has good electromagnetic wave absorption ability, which can increase the surface energy of butyl rubber, thereby improving the physical adsorption capacity of the coating and the substrate. Nanoparticles provide more contact area and interface interaction, which enhances the adhesion of the coating. In addition, maleic anhydride grafts can react with double bonds in butyl rubber to form polymers with carboxyl groups, which can react with amino or hydroxyl groups in the coating to form strong chemical bonds; the properties of the composite nitrile rubber (Comparative Example 3) not dipped in polylactic acid (PLA)-graphene nanosheet ink-based conductive coating have all decreased, especially the electrical conductivity and thermal conductivity have decreased significantly, indicating that the synergistic effect of the composite nitrile rubber and the coating promotes the thermal conductivity, anti-electromagnetic drying and electrical conductivity of the composite butyl rubber. Because under the action of the heat source, the phenomenon of cold water droplets rolling rapidly on the coating surface is related to the increase in temperature between the water droplets and the coating interface. The increase in temperature at the interface between the water droplets and the coating will cause the disappearance of small water droplets in the micro / nano structure, resulting in smoother and faster sliding of the water droplets, thereby playing an effective anti-icing effect. It can be seen that the performance of the multifunctional composite butyl rubber belt prepared by the present invention is greatly improved.

[0071] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a nitrile rubber belt, characterized in that: The following steps are involved: S1. First, add nano-silicon to a mixed solution of ethanol and deionized water, stir, separate the nano-silicon using a centrifuge, remove the supernatant, and wash; S2, adding the nano-silicon cleaned in the above S1 to ethanol, stirring evenly, adding γ-aminopropyltriethoxysilane dropwise under stirring, adding glacial acetic acid to adjust the pH of the solution to acidic, and stirring to obtain an acidic mixture to ensure that γ-aminopropyltriethoxysilane and nano-silicon fully react, and then continue to stir the above acidic mixture at room temperature for 12 hours to promote the hydrolysis and polymerization reaction of γ-aminopropyltriethoxysilane on the surface of nano-silicon; S3, using a centrifuge to separate the nano-silicon modified by the above S2, removing the supernatant, and then washing with ethanol and deionized water for 3 times to remove unreacted γ-aminopropyltriethoxysilane, and drying the treated nano-silicon in a vacuum oven; S4, mixing butyl rubber and maleic anhydride, and reacting them, and then adding nano silicon to the reacted butyl rubber, reacting and stirring; S5, dissolving the butyl rubber after the reaction in the above S4 in a toluene solution, adding zinc oxide, stearic acid, tetramethylthiourea disulfide and sulfur, and then performing ultrasonic treatment to obtain a mixture; S6, treating the single-walled carbon nanotubes in toluene by ultrasonic treatment, and then adding the resultant to the mixture prepared in S5; S7, subjecting the mixture obtained in S6 to ultrasonic treatment again, and drying in a vacuum oven to obtain a dry mixture; S8, hot pressing the dry mixture obtained in S7 to make a rectangular sample of nitrile rubber for standby use; S9, stirring ethyl acetate and benzyl alcohol at room temperature to obtain a solvent mixture for standby use; S10, adding the graphene nanosheets to the solvent mixture of S9, and performing ultrasonic treatment to obtain a mixture for later use; S11, adding a plasticizer to the mixture obtained in S10, and mechanically stirring the mixture until it is completely dissolved; S12, adding dimethylsiloxane and polylactic acid particles to the mixed solution obtained in S11, and magnetically stirring the solution until it is completely dissolved, and finally adding a silane coupling agent and stirring evenly to obtain ink, which is stored for later use; S13, wetting the surface of the rectangular sample of nitrile rubber prepared in S8 above with acetic acid solution, and drying it under a fume hood, and using a strong tape to slightly stretch the rectangular sample of nitrile rubber during drying; S14, spray the ink prepared in the above S12 on the nitrile rubber substrate processed by the above S13 with a spray gun, apply a layer on the nitrile rubber substrate, and dry it. After the sprayed ink is dried, the composite nitrile rubber after the coating is hot-pressed with a press.

2. The method for preparing a nitrile rubber belt according to claim 1, characterized in that: The amount ratio of nano-silicon to ethanol and deionized water in S1 is 1 g:25 mL:25 mL, the stirring time is at least 30 minutes, and the washing is performed at least 3 times.

3. The method for preparing a nitrile rubber belt according to claim 1, characterized in that: The mass ratio of γ-aminopropyltriethoxysilane to nano-silicon in S2 is 1:2, and the pH value of the acidic mixture is 4-5.

4. The method for preparing a nitrile rubber belt according to claim 1, characterized in that: The setting temperature of the vacuum oven in S3 is 60°C and the drying time is 12 hours.

5. The method for preparing a nitrile rubber belt according to claim 1, characterized in that: In the S4, the mass ratio of butyl rubber to maleic anhydride is 20:1, the reaction temperature is 90-110°C, the reaction time is at least 60 minutes, the mass ratio of nano silicon to butyl rubber is 10:1, the reaction temperature is 70-90°C, and the stirring time is at least 30 minutes.

6. The method for preparing a nitrile rubber belt according to claim 1, characterized in that: In the S5, the butyl rubber dissolved in the toluene solution is 30%wt, the weight ratios of zinc oxide, stearic acid, tetramethylthiourea disulfide, sulfur and butyl rubber are 1:20, 3:100, 1:100 and 1:200 respectively, and the ultrasonic treatment time is at least 30 minutes.

7. The method for preparing a nitrile rubber belt according to claim 1, characterized in that: The mass ratio of the single-walled carbon nanotubes to the butyl rubber in the S6 is 1-8:100, the ultrasonic treatment time is 30 min, and the speed of adding the single-walled carbon nanotubes after ultrasonic treatment into the mixture is 1-8 phr.

8. The method for preparing a nitrile rubber belt according to claim 1, characterized in that: The ultrasonic treatment time in S7 is at least 60 minutes, the set temperature of the vacuum oven is 60-80° C., and the drying time is at least 12 hours.

9. The method for preparing a nitrile rubber belt according to claim 1, characterized in that: In S8, the hot pressing temperature is at least 200° C., the hot pressing pressure is at least 2 MPa, the hot pressing time is 80-100 min, and the thickness of the rectangular nitrile rubber sample is 1 mm; The mass ratio of ethyl acetate to benzyl alcohol in S9 is 4:1, and the stirring time is at least 2 hours; The graphene nanosheets in S10 are 30%wt and the ultrasonic treatment time is at least 30 minutes; The plasticizer in S11 is 15%wt, the speed of mechanical stirring is ≥550rpm, and the stirring time is at least 5 minutes; In the S12, dimethylsiloxane is 20%wt, polylactic acid particles are 35%wt, the speed of magnetic stirring is ≥550rpm, the stirring time is at least 24h, and the silane coupling agent is 5%wt; The percentage content of the acetic acid solution in S13 is 100%, and the drying time is at least 15 minutes; In the S14, the spraying distance is set to 100 mm, the pressure is 2.0 bar, the coating thickness is 0.150 mm, the drying time is at least 3 hours, the hot pressing temperature is 50-60°C, the hot pressing pressure is at least 2 kPa, and the hot pressing time is at least 2 minutes.

10. Application of the nitrile rubber tape obtained by the method for preparing the nitrile rubber tape as claimed in claim 1 in the field of flexible electronics and shielding application materials in the aerospace, semiconductor and medical industries.

Citation Information

Patent Citations

  • Preparation method of negative electrode slurry and grafted carbon nanotube

    CN118156483A

  • Conductive wear-resistant nitrile rubber material and preparation method thereof

    CN118909329A